Improvement in survival of patients with oral cavity squamous cell carcinoma: An international collaborative study. Issue 24 (20th September 2013) - Amit, Moran; Yen, Tzu‐Chen; Liao, Chun‐Ta; Chaturvedi, Pankaj; Agarwal, Jai Prakash; Kowalski, Luiz P.; Ebrahimi, Ardalan; Clark, Jonathan R.; Kreppel, Matthias; Zöller, Joachim; Fridman, Eran; Bolzoni, Villaret A.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND An association between the survival of patients with oral cavity squamous cell carcinoma (OCSCC) and advancements in diagnosis and therapy has not been established. METHODS This was a retrospective, longitudinal, international, population‐based study of 2738 patients who underwent resection of OCSCC during 2 different decades. Characteristics of patients from 7 international cancer centers who received treatment between 1990 and 2000 (group A; n = 735) were compared with patients who received treatment between 2001 and 2011 (group B; n = 2003). RESULTS Patients in group B had more advanced tumors and tended to develop distant metastases more frequently than patients in group A (P = .005). More group B patients underwent selective neck dissection and received adjuvant radiotherapy (P < .001). Outcome analysis revealed a significant improvement in 5‐year overall survival, from 59% for group A to 70% for group B (P < .001). There was also a significant improvement in disease‐specific survival associated with operations performed before and after 2000 (from 69% to 81%, respectively; P < .001). Surgery after 2000, negative margins, adjuvant treatment, and early stage disease were independent predictors of a better outcome in multivariate analysis. The decade of treatment was an independent prognostic factor for cancer‐specific mortality (hazard ratio, 0.42; 95% confidence interval, 0.3‐0.6). CONCLUSIONS The survival rate of patients with OCSCC improved significantly during the past 2 decades despite older age, more advanced disease stage, and a higher rate of distant metastases. The current results suggest that the prognosis for patients with OCSCC has improved over time, presumably because of advances in imaging and therapy. Cancer 2013;119:4242–4248. © 2013 American Cancer Society.